Hot rocks : 1964-1971 [compact disc] - Jagger, Mick; Richards, Keith, 1943-; Jones, Brian, 1942-1969; Wyman, Bill; Watts, Charlie; Oldham, Andrew Loog; Phelge, Nanker (Abkco, 2002)
Showcasing the evolution of the Rolling Stones from a blues-rock band to one of rock's most successful acts, this two-disc set includes hits like (I Can't Get No) Satisfaction.